Sistem Informasi Buku Tamu Berbasis Website pada Kantor Badan Pertanahan Nasional Kota Medan - Nasution, Adnan Buyung; Faisal, Ibnu; Panggabean, Disnu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The web-based guest book information system is an innovative solution designed for easy and efficient management of guest books at the National Land Agency office in Medan City. Using the PhpMyAdmin database system, an open-source web-based program built to simplify guest book management. The focus of this research is on the web-based guest book information system, which makes it easy for employees to record and monitor guest data at specific times. This research uses the Waterfall Method, a software built using a methodical and sequential approach in the classic model. The results of this study show that the web-based guest book information system is an effective solution for managing data and monitoring guest visits at the National Land Agency office in Medan City. Using web technology, guest information can be accessed quickly and accurately.